The Development of Snake Ladder Game Media in Compound’s Nomenclature Subject for Tenth Graders at SMAN 16 Banda Aceh - Habibati Habibati; M Hasan; Ria Afriza (Proceedings of AICS - Social Sciences, 2017)
This study aims were to: (1) examine the expediency of snake ladder game media (2) know students’ learning outcome, (3) evaluate the students’ response towards the developed snake ladder game media in compound’s nomenclature subject. The research type used was Research and Development (RD) with ADDIE development model. Data collection techniques used was media expediency questionnaire, observation, the cognitive test, and students’ response questionnaire. The research’s instruments used were media expediency questionnaire sheet, students’ activity observation sheet, test questions, and students’ response questionnaire sheet. The study results were obtained (1) the average percentage of media expediency questionnaire sheet from two validators was 100% which was in very proper category, (2) classically, the percentage of students’ who gained mastery level was 80%, and 3) the average percentage of students’ response was 81,87% within very well category. To conclude, snake ladder game media could increase students’ performance on the subject of compound’s nomenclature.